Damage and repair of subsea pipeline in shallow gas area - Xiufeng LI; Ying ZHANG; Biao FENG (You-qi chuyun, 2020)
A 10-in (1 in = 2.54 cm) subsea oil pipeline and a 14-in gas pipeline of an oilfield crosses a shallow gassubsidence area at about 53 km (KP53) away from the landing point of Hangzhou Gulf. These two pipelines have beenin service for nearly 20 years, but each damaged happened after typhoon. Cause analysis was carried out based on theinvestigation data of damage accidents of oil pipeline crossing the shallow gas subsidence area, and it was found that thepipeline fracture was caused by the fatigue load due to soil liquefaction and subsidence during typhoon. Thereby, a repairplan was designed according to the engineering characteristics for guidance of pipeline repair construction. The repairedpipeline has been subject to several times of typhoon and it is still in good conditions. The research results are of guidingsignificance to the construction of submarine pipeline crossing shallow gas geological hazard area or the seabed with soilliquefaction trend.